2012
DOI: 10.1002/app.38300
|View full text |Cite
|
Sign up to set email alerts
|

UV‐activated hydrosilation reaction for silicone polymer crosslinking

Abstract: In this article hydrosilation was employed to achieve a fully cured three-dimensional silicone network. The UV-activated hydrosilation reaction was investigated focusing on the curing conditions and their relationships to physical properties. After finding the optimum catalyst concentration, it was observed that by decreasing the molecular weight of the vinyl oligomer a slight increase of the T g value was achieved together with a complete suppression of the Tm. It was possible to fully cure samples up to 4 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 16 publications
3
29
0
Order By: Relevance
“…In literature, this phenomenon was attributed to the formation of a heterogeneous specie that catalyzes the hydrosilation reaction. [ 8,9,15 ] This proceeding of the curing in the dark was also reported in our previous papers for a different silicone system [ 13,14 ] and was attributable to the activation of a front process.…”
Section: Dark-curingsupporting
confidence: 83%
“…In literature, this phenomenon was attributed to the formation of a heterogeneous specie that catalyzes the hydrosilation reaction. [ 8,9,15 ] This proceeding of the curing in the dark was also reported in our previous papers for a different silicone system [ 13,14 ] and was attributable to the activation of a front process.…”
Section: Dark-curingsupporting
confidence: 83%
“…In order to evaluate the presence of a dark curing (that is, the proceeding of the curing without UV light), silane conversion was followed by FTIR analyses after different times of irradiation. A significant increase of the Si-H conversion in the dark for the Pt(acac) 2 catalyst was previously reported [13] and was attributed to the slow conversion of the homogeneous hydrosilation catalyst (formed under UV irradiation) into a less active heterogeneous catalyst, similar to the one formed upon thermal hydrosilation reaction. [7,13,14] Mixtures containing equimolar amount of PDMS-V and MH-PDMS with 250 ppm (Figure 2a) and 1 000 ppm ( Figure 2b) of (Me-Cp)Pt(Me) 3 catalyst were investigated.…”
Section: Evaluation Of the Dark Curingsupporting
confidence: 66%
“…A significant increase of the Si-H conversion in the dark for the Pt(acac) 2 catalyst was previously reported [13] and was attributed to the slow conversion of the homogeneous hydrosilation catalyst (formed under UV irradiation) into a less active heterogeneous catalyst, similar to the one formed upon thermal hydrosilation reaction. [7,13,14] Mixtures containing equimolar amount of PDMS-V and MH-PDMS with 250 ppm (Figure 2a) and 1 000 ppm ( Figure 2b) of (Me-Cp)Pt(Me) 3 catalyst were investigated. The mixtures were coated on a SiC substrate with a thickness of 50 mm and then irradiated with UV light for 10, 30, and 60 s, respectively.…”
Section: Evaluation Of the Dark Curingsupporting
confidence: 66%
See 1 more Smart Citation
“…The curing of the polymeric matrix was achieved by UV‐induced hydrosilation reaction, which we investigated in a previous paper . It was also demonstrated that the hydrosilation reaction proceeds by a thermal‐frontal mechanism allowing to have 3 cm thick homogeneous unfilled sample .…”
Section: Introductionmentioning
confidence: 99%